2017
DOI: 10.1039/c6ra28742e
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from amino functionalized graphene quantum dots prepared by electrochemical exfoliation method in the presence of ammonium ions

Abstract: This study elucidates how the nitrogen functionalities affect the UV-visible absorption and photoluminescence (PL) emission of N-modified graphene quantum dots (NGQDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…These peaks confirm the presence of various functional groups such as carbonyl, carboxylic, etc. over the surface of as-synthesized WS 2 -QDs, which is also in good agreement with the FTIR analysis. Further, the BE of O 1s core level peak in the region 528–535 eV can be fitted into doublet peaks at 530.1 and 531.4 eV (shown in Figure d).…”
Section: Resultssupporting
confidence: 87%
“…These peaks confirm the presence of various functional groups such as carbonyl, carboxylic, etc. over the surface of as-synthesized WS 2 -QDs, which is also in good agreement with the FTIR analysis. Further, the BE of O 1s core level peak in the region 528–535 eV can be fitted into doublet peaks at 530.1 and 531.4 eV (shown in Figure d).…”
Section: Resultssupporting
confidence: 87%
“…The PL QYs of the O-NGQDs and B-NGQDs samples were 22.9% and 1% for the emission at 380 nm, respectively. The prominent increase of QY is due to the existence of surface functional species, which has been proven by many studies. ,, The quantum yield (φ) of O-NGQDs is higher than in some previous reports (shown in Table S1). , The average lifetimes were 6.67 and 4.78 ns, respectively.…”
Section: Results and Discussionmentioning
confidence: 72%
“…The graphene nanosheets (GN) were separated by size using polymeric filters, and NGQDs were collected through centrifugation. The resulting NGQDs displayed greater amination levels when synthesized with lower applied potentials, as the rate of GN exfoliation was slower, allowing sufficient in situ functionalization with the ammonium ions in the solution 87. Zhang et al.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The resulting NGQDs displayed greater amination levels when synthesized with lower applied potentials, as the rate of GN exfoliation was slower, allowing sufficient in situ functionalization with the ammonium ions in the solution. [87] Zhang et al demonstrated the synthesis of boron-functionalized GQDs by doping graphite rods; XPS spectra verified the presence of boron functional groups on the synthesized GQDs. [88] Electrochemical synthesis provides a pathway for more precise synthesis of GQDs compared to hydro/solvothermal methods, by selectively oxidizing the precursor material according to the applied electric potential.…”
Section: Electrochemical Exfoliationmentioning
confidence: 99%